Factors Influencing Efficacy of Complete Decongestive Treatment in Patients with Breast Cancer-Linked Arm Lymphoedema - Bojinović-Rodić, Dragana; Pjanić, Samra; Popovic, Tamara; Nožica-Radulović, Tatjana (Scripta Medica, 2021)
Background/Aim: The most recommended form of lymphoedema therapy is com-plete decongestive treatment (CDT). Efficacy of CDT in patients with arm lymph-oedema related to malignant breast tumour has reported in many studies, but the predictive factors of outcome of this therapy have not been yet sufficiently investi-gated. The purpose of this research was to identify predictive factors of efficacy of CDT in patients with breast cancer-linked arm lymphoedema throughout the inten-sive phase of therapy. Methods: The prospective study included 51 patients with breast cancer-linked arm lymphoedema who were subjected to a 3-week program of CDT. Patients’ clini-cal and demographic features, breast cancer treatment characteristics, lymphoede-ma and CDT characteristics were collected and assessed for their prognostic value. The influence of certain predictors on the degree of lymphoedema reduction was evaluated by multivariate linear regression analysis. Results: Mean age was 58.1 ± 8.0 (95 % CI: 55.8 - 60.3), median of BMI was 28.4 kg/m2 (95 % CI: 27.2 - 29.6). The average duration of lymphoedema was 36.5 ± 43.9 months (95 % CI: 24.1 - 48.8). The mean size of lymphoedema before CDT was 6.99 ± 5.36 %, and the mean degree of lymphoedema reduction was 63.7 ± 28.6 %. The mean compliance to bandages was 217.5 ± 97.8 hours (95 % CI: 190.0 - 245.0) and 7 (13.7 %) patients had a history of erysipelas of the ipsilateral arm. When observ-ing each individual predictor, statistically most significant contribution showed the size of lymphoedema before the therapy (p < 0.001), then history of erysipelas (p < 0.01), and patients’ age (p < 0.05). Conclusion: Size of lymphoedema before treatment is the most crucial prognostic factor of the efficacy of CDT in the patients with breast cancer-linked arm lymph-oedema. The present study also identified history of erysipelas and patients age as independent predictors of the CDT efficacy.